The new testament - Brown, Jericho (2014)
""Erotic and grief-stricken, ministerial and playful, Brown offers his reader a journey unlike any other in contemporary poetry."--Rain Taxi"To read Jericho Brown's poems is to encounter devastating genius."-Claudia RankineIn the world of Jericho Brown's second book, disease runs through the body, violence runs through the neighborhood, memories run through the mind, trauma runs through generations. Almost eerily quiet in even the bluntest of poems, Brown gives us the ache of a throat that has yet to say the hardest thing-and the truth is coming on fast. Fairy TaleSay the shame I see inching like steam Along the streets will never seep Beneath the doors of this bedroom, And if it does, if we dare to breathe, Tell me that though the world ends us, Lover, it cannot end our love Of narrative. Don't you have a story For me?-like the one you tell With fingers over my lips to keep me From sighing when-before the queen Is kidnapped-the prince bows To the enemy, handing over the horn Of his favorite unicorn like those men Brought, bought, and whipped until They accepted their masters' names. Jericho Brown worked as the speechwriter for the mayor of New Orleans before earning his PhD in creative writing and literature from the University of Houston. His first book, PLEASE (New Issues), won the American Book Award. He currently teaches at Emory University and lives in Atlanta, Georgia."--
Colosseum -- Romans 12:1 -- Heartland -- Another elegy -- Cain -- Labor -- The interrogation -- Paradise -- To be seen -- Langston's blues -- "N'em -- The ten commandments -- Homeland -- Host -- Football season -- The rest we deserve -- What the Holy do -- Reality show -- Willing to pay -- Dear Dr. Frankenstein -- Another Elegy -- Motherland -- 1 Corinthians 13:11 -- Hustle -- Another elegy -- Obituary -- Psalm 150 -- A living -- After the rapture -- Hebrew 13 -- Angel -- Receiving line -- Make-believe -- Found : Messiah -- Another angel -- Eden -- Another elegy -- At the end of hell -- Heart condition -- Nativity
"Lannan literary selection."
"First printing."
Keywords: American poetry -- 21st century; American poetry -- 21st century; Poetry; Poetry